Оцінка специфіки алелофонду деяких порід свиней - Бодряшова, К.В.; Парасочка, І.Ф. (Фактори експериментальної еволюції організмів, 2015)
Aims. To evaluate particularities of immunogenetic structure of certain pig breeds, which are breeded in Ukraine.
Methods. Studies were conducted at the main farms for pig breeding of: Large White, Large Black, Mirgorodska and
Duroc. Red blood cell antigens have been identified, immunogenetic parameters and differentiation of populations
allele pool have been studied. Results. This article highlights objective evaluation of their genetic variability degree and
defines differentiation of populations allele pool by genetic distances and their immunogenetic similarity. Conclusions.
Particularity in assayed pigs populations characterizes by certain differences in relations of appropriate alleles. Pairwise
comparison of breeds by genetic distances revealed the biggest similarity of Large White and Mirgorodska breeds by
alleles of nine blood groups systems.
Keywords: immunogenetic markers, differentiation, gene pool, pig breeds.